Wali Perempuan Dalam Al-Qur’an - Abdur Rohman (Realita: Jurnal Penelitian dan Kebudayaan Islam, 2020)
The term female guardian may still be foreign to Javanese ears, especially women in the Qur'an. This article will discuss about female guardians from the point of view of a thematic interpretation. The conclusion of this article is: a person's barometer is said to be a guardian if three elements are fulfilled, namely a holy person, having a sacred spirit, and not feelingÂ afraid or sad. There are three names for female guardians in the Koran. First, Maryam, a holy man, an expert in worship, never had sexual relations but was gifted with a child directly from Allah. He can also communicate with the angel Gabriel. Second, 'Imra'ah Fir'awn, namely a holy girl who can still maintain her chastity even though she is the wife of an unjust and infidel king. He was also able to defend his faith amidst the glitter of wealth and the royal family that was pagan and full of pressure. Third, Ummi Musa, a holy woman who is able to communicate with the angel Gabriel and has closeness to God.